2015
DOI: 10.1007/s11665-015-1822-5
|View full text |Cite|
|
Sign up to set email alerts
|

Initiation of Stress Corrosion Cracks in X80 and X100 Pipe Steels in Near-Neutral pH Environment

Abstract: Tests were conducted on X80 and X100 pipe steels at 95% specified minimum yield stress in NS4 solution mixed with soil using specimens machined along the transverse direction of the pipes. Crack initiation in X100 is much easier than in X80. With test time increasing from 110 to 220 days, less numerous but deeper cracks were found in both pipe steels. Cracks showed higher growth rates in the transverse specimens than those in longitudinal ones. TEM results revealed concentration of Ni or Cr elements, formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Note that internal pressures in pipelines are generally fluctuating, resulting in cyclic stresses in the pipeline. Although small-scale tests reported in [38][39][40][41] have shown that cracks can initiate and propagate in specimens in an NNpH environment under quasi-static and static loading conditions, extensive full-scale tests [42,43] have demonstrated that cyclic stress facilitates the propagation of NNpH cracks far more than static stress. The present study considers CF enhanced by HE as the main mechanism for the growth of NNpH cracks.…”
Section: Nnphscc On Pipelinesmentioning
confidence: 99%
“…Note that internal pressures in pipelines are generally fluctuating, resulting in cyclic stresses in the pipeline. Although small-scale tests reported in [38][39][40][41] have shown that cracks can initiate and propagate in specimens in an NNpH environment under quasi-static and static loading conditions, extensive full-scale tests [42,43] have demonstrated that cyclic stress facilitates the propagation of NNpH cracks far more than static stress. The present study considers CF enhanced by HE as the main mechanism for the growth of NNpH cracks.…”
Section: Nnphscc On Pipelinesmentioning
confidence: 99%
“…Extensive research has been carried out targeting different aspects of NNpHSCC, such as the failure mechanism, [5][6][7] crack initiation, [8][9][10][11][12] and crack growth quantification and modeling. [13][14][15][16][17][18] Full-scale testing 10,19 using soil boxes that simulate the field condition provides a viable means to directly evaluate the SCC crack propagation behaviors at different internal pressure levels, ranges of pressure fluctuation, and soil conditions. This type of test also allows a direct validation of SCC growth models.…”
Section: Introductionmentioning
confidence: 99%
“…This type of test also allows a direct validation of SCC growth models. Since the 1990s, the CanmetMATERIALS Laboratory of Natural Resources Canada 16,19,20 has conducted such tests extensively and found that the crack depth growth rates per unit time (da/dt) are in the range of 5 Â 10 À9 mm/s (0.16 mm/ year) and 1 Â 10 À5 mm/s (315 mm/year) under different loading and environmental conditions. The Canadian Energy Pipeline Association (CEPA) estimated the timeaveraged crack growth rates on two in-service pipelines that failed due to NNpHSCC to be 0.3 and 0.63 mm/year, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect has been mainly attributed to a reduced rate of dissolution at the crack tip in the depth direction [11,12]. Although crack dormancy is manifested [1,[12][13][14][15][16], the corrosion process could continue, and if so, it can increase blunting and stagnate the solution inside the crack, thereby affecting the probability of re-activation [15]. Evidence also pointed out the existence of two sequential mechanics for the initiation and early-crack growth of transgranular SCC; first, the anodic dissolution (AD) leading to pitting [17][18][19] and then the hydrogen embrittlement (HE) by means of acidification within these pits [20,21].…”
Section: Introductionmentioning
confidence: 99%